1987
DOI: 10.1002/cjce.5450650512
|View full text |Cite
|
Sign up to set email alerts
|

The influence of geometrical factors and feedstock on gasification in a high temperature fluidised bed

Abstract: Results are presented for gasification of coal and char by means of air or air‐steam mixtures in fluidised bed reactors of three different volumes. Two sizes of coal feedstock particles, 0.5‐1.0 mm and 1.0‐1.5 mm, and one size of char particles, 0.5‐1.5 mm, were used. The calorific value of generated gas and the carbon conversion are presented as a function of particle residence time. For coal gasification higher carbon conversion has been obtained at the same particle residence time than for char gasification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Similar results are also reported by Gil et al [32] for gasification of pine wood chips. While studying the influence of particle size and reactor geometry in a fluidized bed gasification of coal and coal-derived char, Tomeczek et al [33] observed that char required more residence time than coal to produce product gas of the similar calorific value. Pan et al [16] observed that the superficial velocities of 0.76-1.45 m/s were too high or in other words residence times 1.7-3.5 s were too low, to achieve water-gas shift reaction equilibrium conditions.…”
Section: Air and Steam Flowmentioning
confidence: 99%
“…Similar results are also reported by Gil et al [32] for gasification of pine wood chips. While studying the influence of particle size and reactor geometry in a fluidized bed gasification of coal and coal-derived char, Tomeczek et al [33] observed that char required more residence time than coal to produce product gas of the similar calorific value. Pan et al [16] observed that the superficial velocities of 0.76-1.45 m/s were too high or in other words residence times 1.7-3.5 s were too low, to achieve water-gas shift reaction equilibrium conditions.…”
Section: Air and Steam Flowmentioning
confidence: 99%
“…Nevertheless, these models assume steady‐state conditions, which do not fully represent the reality of fluidized bed gasifiers. Furthermore, certain emulsion phase particles experience intraparticle mass transfer phenomena and changes in porosity and reactivity 4,14,15 which these models do not account for.…”
Section: Introductionmentioning
confidence: 99%